Demographic Effects on the Sources of Guidance Used by Nigerian and UK Managers (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The aim of this study was to determine the effects of demographic variables such as age, gender, organization size and organization ownership on the sources of managerial guidance most often used by managers from Nigeria and UK. The guidance sources included formal rules, unwritten rules, subordinates, specialists, co-workers, superior, own experience and widespread beliefs as to what is right. Data were collected from 288 Nigerian and 141 UK managers. UK managers reported relying most frequently on their own experience, Nigerian managers reported relying most strongly on formal rules. Hierarchical regressions showed that reliance on formal rules, on superiors, on unwritten rules and on subordinates were significantly related to demographic predictors. However, the demographic predictors of reliance on these sources differed between the two countries and these differences are interpreted in terms of differences in national culture.